Zawarcie umowy w świetle praktyki jednostek gospodarki uspołecznionej: [Conclusion of a contract in the light of practice in units of the socialized economy] (Studia Prawnicze / The Legal Studies, 1982)
Conclusion of the contracts in relations between units of the socialized eco- nomy is regulated by numerous special provisions which, however, modify and widen civil code’s general regulation only to a small extent.Against the background of these special provisions, full freedom as to the choice of procedure of conclusion of a contract is even more distinct. Various existing limitations of facturai nature are a different matter.Beside the procedure of negotiation and offer, also other combined procedures are admissible in relations between units of the socialized economy. These are various combinations of both aforementioned procedures.As practice of units of the socialized economy shows, parties enter into negotiations while concluding contracts of greater importance. Principle expressed in article 73 of the civil code, i.e. that in case of doubt a contract is considered concluded when the parties reach an understanding as to all those provisions which were the object of the negotiations, is respected, although the part of legal doctrine is of the opinion that it should not be binding in relations between units of the socialized economy, especially in case one of the parties is bound by the duty to conclude a contract.Conclusion of contracts following offer and acceptance procedure is characteristic especially for trade in goods. This procedure is partly modified and causes some difficulties. In particular, we observe conclusion of contracts even though an offer was accepted as to a part of the promised performance only. This motivates our thesis that an offerent consents to offeree’s changing of contents of the offer. In case of conlusion of contracts in the form of the so called organized transit, such right to change the offer is either expressed or implied, and to the organizer of transit. According to article 399 of the civil code an offeree may conclude a contract although he accepted the offer with reservations by simultaneously signing a protocol of divergence. This argues for the thesis that even though an offer was accepted with reservations, a contract is concluded. On the other hand, protocol of divergence constitutes an offer to conclude another contract specifing contents of the relationship created by the first contract.Special provisions regulating conclusion of some contracts introduce a com- bination of offer and negotiation procedures (this concerns especially contracts relating to carrying out of investment processes). Thus, various ways of conclusion of a contract are possible, depending upon whether the addressee of an order consents right away to proposed conditions, or whether the parties reach an under- standing as to the contents of contract in results of negotiations carried out on the basis of that order and then conclude a contract, or else, whether the negotiations serve only as a basis for a project of contract which is later treated as an offer to conclude a contract.Special provisions do not introduce specific changes as to the form of contracts. On the other hand, they introduce provisions defining possible ways of fulfilling requirements concerning the form in writing.So called „transit”, and especially organized transit, common in relations between units of the socialized economy, cause many legal problems. Basic difficulty here is to define the character of legal relationship between the organizer of transit and unit of socialized economy for the benefit of which the organizer acts, since these relationships are often created regardless of the will of the in- terested parties.Concluding, we should state that general regulation of procedure contained in the Civil Code relating to conclusion of contracts, is fully adaptable to relations between units of the socialized economy and requires only small supplementation; as for binding special provisions, it would only be advantageous if they were formulated in a more general way.